Caracterização tecnológica do Itabirito pobre compacto IPC da Mina Casa de Pedra - Erica de Queiroz Ribeiro (2011)
This study presents the mineralogical and technological characterization of the Itabirito Pobre Compacto - IPC's of Mina Casa de Pedra. The IPC is a material with average iron content of 42% and has high mechanical strength. The combination of these characteristics makes it impossible to processing this material in the processing plant of the Casa de Pedra, since its feeding would contaminate the sinter feed and pellets products. Thus the IPC until then was considered sterile. This material represents 30% of the reserve of the Casa de Pedra mining. The technological characterization, object of this work, included a detailed study of important variables of the flotation process for the processing of IPC after grinding for liberation. The main focus was to evaluate the influence of collectors ethermonoamine and etherdiamine in various dosages and mixtures of collector with frothers at different pH values. To characterize the material, particle size distribution, chemical analysis, X-ray diffraction and optical microscopy data were analyzed. The results achieved show that the IPC can be used to obtain the pellet feed, through milling and concentration by the process of reverse cationic flotation